Ready to go? The importance of being prepared for flood disaster - Aung, Khin Thandar; Nurumal, Mohd. Said; Abdul Rahman, Nurul 'Inayati; Ahayalimudin, Nurul'Ain (Scholars Academic and Scientific Publisher (SAS Publisher), 2017)
There is a growing awareness that disasters can strike anytime and anywhere. On an average, a disaster occurs in everyday somewhere in the world. Many developing countries, have limited preparedness for disaster response. Preparedness means preparing to handle an emergency and include plans or preparations made to save lives and to help response and rescue operations. If a disaster occurs in the community, local government and disaster-relief organizations will try to help the victim, but the victim itself needs to be ready as well. Local responders may not be able to reach the victim immediately, or they may need to focus their efforts elsewhere. The victim should also be ready to be self-sufficient for at least three days. This may mean providing for own shelter, first aid, food, water, and sanitation. This review paper aimed to study the impact of disaster preparedness, importance of preparedness in flood disaster, ways of emergency preparedness for flood disaster and benefits of preparedness for flood disaster.